Capture of 60 men of the 23rd S.C. Regt. - Valentine, Herbert E. (My University, 1862)
Kinston N.C. Dec. 13th or 14th 1862. I well remember the taking of these men. The 23rd Mass. was halted near one side of a large field close by a wall that ran down the slope at right angles to another wall which made on e side of the field. Near the intersection of the 2 walls was an opening between the two fields, the bars being down. Through this opening came a large body of men, the foremost one waving a handkerchief or a piece of white cloth. Major Chambers of our regiment made a dash for the Squad, and a Captain of a battery followed closely. The Major came out ahead, receiving the surrender of the men the 23rd Mass getting the credit of their capture.
Keywords: Kinston (N.C.); Massachusetts Infantry. 23rd Regiment.; Prisoners and Prisons; South Carolina Infantry. 23rd Regiment